Efficient production of biodiesel from palm fatty acid distillate using a novel hydrochar-based solid acid catalyst derived from palm leaf waste - Aliyu, Muhammad; Moser, Bryan R.; Alharthi, Fahad A.; Rashid, Umer (Institution of Chemical Engineers, 2024)
To combat fuel shortages, pollution, and the exhaustion of natural oil resources, an environmentally friendly alternative to fossil fuels, such as biodiesel, is essential for meeting global transportation demands. A novel heterogeneous acid catalyst for production of biodiesel from low-cost, high free fatty acid feedstocks was synthesized in this study by activating and impregnating hydrochar from palm leaf (PL) waste with H3PO4 and H2SO4. Subsequently, the sulfonated catalyst was utilized for the esterification of palm fatty acid distillate (PFAD). FT-IR, XRD, FESEM, EDX, BET, TGA, and surface acidity methods were employed to characterize the acid catalyst. Using the one-variable-at-a-time (OVAT) technique, the optimized reaction conditions for esterification of PFAD using the hydrochar-based catalyst were 4 wt% catalyst loading, 353.15 K reaction temperature, 4 h reaction time, and 18:1 methanol: PFAD molar ratio. At these conditions, a maximum biodiesel yield of 93.56% was achieved. The catalyst exhibited excellent reusability and stability throughout five reaction cycles, maintaining biodiesel yields above 80% after each cycle. Analysis of the fuel properties revealed that the biodiesel derived from PFAD met the physiochemical criteria outlined in ASTM D6751, the American biodiesel standard. The kinetic study revealed that the esterification reaction followed pseudo-first-order kinetics with an activation energy (Ea) of 23.70 kJ/mol. Furthermore, the thermodynamic enthalpy (∆H*) and Gibbs' free energy (∆G*) of esterification were 20.9 and 33.41 kJ/mol, respectively, indicating that the reaction was an endothermic and non-spontaneous process.